2023
DOI: 10.1371/journal.pone.0291956
|View full text |Cite
|
Sign up to set email alerts
|

Demographic dynamics between 5500 and 3500 calBP (3550–1550 BCE) in selected study regions of Central Europe and the role of regional climate influences

Ralph Großmann,
Mara Weinelt,
Johannes Müller

Abstract: With their rich Late Neolithic to Early Bronze Age archives, the Circumharz region, the Czech Republic/Lower Austria region, and the Northern Alpine Foreland are well-suited for research on potential links between human activities and climate fluctuations of this period with pronounced archaeological changes. In this paper, we reconstruct the rate and density of the available 14C data from 5500 to 3500 calBP (3550–1550 BCE). We ask to what extent population patterns varied over time and space, and whether fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…The most recent approach is based on the assumption that more people = more sites = more 14 C dates, and on the statistical correlations between population fluctuations and palaeoclimate records derived from high-resolution speleothems in Central Europe from the Late Neolithic to the beginning of the Middle Bronze Age (5500-3500 cal BP) (Großmann et al 2023). The authors suggest that they found statistical correlations between population fluctuations and climate.…”
Section: Rapid Climate Changes Prehistoric Cultures and The Collapses...mentioning
confidence: 99%
“…The most recent approach is based on the assumption that more people = more sites = more 14 C dates, and on the statistical correlations between population fluctuations and palaeoclimate records derived from high-resolution speleothems in Central Europe from the Late Neolithic to the beginning of the Middle Bronze Age (5500-3500 cal BP) (Großmann et al 2023). The authors suggest that they found statistical correlations between population fluctuations and climate.…”
Section: Rapid Climate Changes Prehistoric Cultures and The Collapses...mentioning
confidence: 99%
“…In the continental but at the same time relatively arid conditions of Central Germany from the Holocene Thermal Maximum to the 4.2kyr event [21][22][23][24], the consumption of lipids through fat-rich food may have been more critical for human nourishment than in more temperate and southern regions, where a broader array of plant resources was available since the beginning of the Neolithic [25,26]. Amongst the existing lipid-rich resources in the Central German Neolithic, the existing faunal analyses show that cattle were the most important domesticate across time while sheep, goat, and pig were of secondary importance and hunting played only a minor role [27].…”
Section: Introductionmentioning
confidence: 99%